Shari'ah compliant construction marketing - development of a new theory - Preece, Christopher Nigel; Abdul Rashid, Khairuddin (2009)
As more socially and environmentally conscious consumers, investors and wider stakeholders have started to question the business practices of organizations, so firms have had to review their business and marketing strategies, the way they produce their products and deliver services from a corporate social responsibility (CSR) and business/marketing ethics standpoint. The construction industry has a generally poor reputation with it's clients/customers, communities and the general public. Marketing is still a relatively new field in the construction services sector. For some professional firms it is still considered to be unethical. However, greater liberalization in developed and developing countries has seen increased use of marketing tactics by construction consultants and contractors. Islam places great importance on equity and justice, this being absolute and not relative, therefore business is not about maximizing profit alone. It is about ibadah [an act of worship], to facilitate and not constrain transactions between people. Goods and services are for all irrespective of class or affordability. Thus the charges/price should be the lowest possible and therefore unnecessary costs should be removed. A business must not be mixed with non-shari'ah compliant practices [e.g. dealing in forbidden acts/products, hoarding, black marketeering, riba, etc], being honest and truthful in conducting transactions [not corrupt], to avoid gharar or risk [with proper assessment, declaration, etc], adhere and deliver promises made [i.e. contracts], and be diligent in undertaking work. This paper will attempt to propose a new Shari'ah compliant theory of construction marketing. It will look at conventional marketing theory elements i.e. decisions concerning product, price, promotion, place and people (the 5 p's), and compare and contrast with the evidence found in the al-Qur'an and as-Sunnah. Broadly, Islam says that a business practice is considered allowable or Shari'ah complaint unless there is a nas (clearly stated in the al-Qur'an, as-Sunnah, al-ijtihad, alijma,) that prohibits it. By applying Shari'ah principles in construction marketing, firms and the Industry in general could improve their practices and reputation.